Formation of a room temperature stable Fe-V(O) complex: reactivity toward unactivated C-H bonds - Ghosh, Munmun; Singh, Kundan K.; Panda, Chakadola; Weitz, Andrew; Hendrich, Michael P.; Collins, Terrence J.; Dhar, Basab B.; Sen Gupta, Sayam (Journal of American Chemical Society, 2014)
An Fe-V(O) complex has been synthesized from equimolar solutions of (Et4N)(2)[Fe-III(Cl)(biuretamide)] and mCPBA in CH3CN at room temperature. The Fe-V(O) complex has been characterized by UV-vis, EPR, Mossbauer, and HRMS and shown to be capable of oxidizing a series of alkanes having C-H bond dissociation energies ranging from 99.3 kcal mol(-1) (cyclohexane) to 84.5 kcal mori (cumene). Linearity in the Bell-Evans-Polayni graph and the finding of a large kinetic isotope effect suggest that hydrogen abstraction is engaged the rate-determining step.